Pulmonary resections: Round Table 29 Uruguayan Congress of Surgery; coordinator Valentín L Crosa - Crosa Dorado, Valentín L; Mezzera, Julio R; Nin Vivo, Jorge; Brandolino, Mario V; Sanjinés, Aníbal (Cirugía del Uruguay, 1979)
The subject is approached from the viewpoint of the general surgeon faced with technical difficulties during the course of the more frequent or feasible puimonary resections atypical parcial resections and right and left upper lobectomies.